The Impact of Trustworthiness on the Association of Corporate Social Responsibility and Irresponsibility on Legitimacy - Hadani, Michael (Journal of Management Studies, 2024)
AbstractResearch on corporate social responsibility (CSR) and corporate social irresponsibility (CSIR) has long argued both affect firms' legitimacy, for good or bad. Such research has ignored how ex‐ante corporate trustworthiness and associated attributions affect the association of CSR and CSIR on corporate normative legitimacy. Focusing on two unique aspects of corporate normative legitimacy evaluations – affect and misconduct – we argue that ex‐ante perceptions of firm trustworthiness moderate the associations among CSR and CSIR and different aspects of normative legitimacy. Utilizing comprehensive panel‐data analytical approaches for S&P 500 firms from 2000 to 2015, MSCI‐KLD data, mass‐media‐based measures of firm trustworthiness, including normative affect‐based legitimacy, and normative misconduct‐related‐legitimacy, our proposition is mostly supported, with surprising caveats. A post‐hoc analysis shows these associations vary based on public versus investors' affective‐legitimacy views. The findings of this study critically challenge extant scholarship and call for a nuanced view of the impact of CSR and CSIR on firm legitimacy.